Integrating zakat, waqf and sadaqah: myint myat phu zin clinic model in Myanmar - Htay, Sheila Nu Nu; Syed, Ahmed Salman (2013)
The Muslim population in Myanmar is approximately eight milllions out of fifty eight millions of the whole population. Majority of the Muslim in Myanmar are the poor and unfortunate and there is a urgent need for them to get help especially in the case of health. When the background of the country is relooked, there are very limited donators for waqf, zakat and sadaqah. However, fortunately, a group of Muslims has founded the clinic by integrating the concepts of the waqf, zakat and sadaqah. It is the first clinic in Myanmar which is established based on the combination of these three concepts for Muslims and non-muslims. Therefore, in this paper, we present a clinic model that integrates three traditional Islamic tools such as waqf, zakat and sadaqah. Moreover, the managment of sources and uses of funds of the clinic is elaborated and explained. It is believed that this clinic model can be used as a model in any other non-Muslim countries with minority Muslim population.